Preparing Regular/Special Education Teachers for Rural Schools: Perceptions of Interest and Capability - David Yellin (Journal of Research in Rural Education, 1988)
This paper focuses on data collected as part of an evaluation of an ongoing rural special education personnel preparation grant being carried out at Oklahoma State University. Participants in the program work toward dual certification in elementary and special education in response to the needs of rural schools. Participants were recruited as college juniors and included those who expressed a strong desire to teach in rural schools in Oklahoma. Data were collected to evaluate change in participant attitudes and perceptions during the first year of participation in the program. Data which are reported come from two instruments which were designed locally. The Rural School Inventory (RSI) focuses on the prospective teacher's attitudes toward working in a rural school and in a rural community. The Educational Practice Inventory (EPI) was derived from Reynolds, Birch, Grohs, Howsom, and Morsink [12] ten Clusters of Capability. It measures the prospective teacher's perceptions of the importance of various teacher competencies, as well as perceptions of one's own capabilities with respect to nine of the ten Clusters. Data were collected upon entry into the program and at the beginning of the second year in the program (Fall, 1986). Results indicate that students in the program are very positive in their attitudes about working in rural schools, but may hold unrealistically high evaluations of their own competence in meeting the diverse needs of children.